Notes for supporting an epistemological neuropsychology : contributions from three perspectives (2013)
ABSTRACT: A review of the epistemological basis of neuropsychology is done in order to clarify its foundations and its dual status as a discipline rooted in biology and psychology. This work is justified from two fundamental issues that are faced by neuropsychology: from an external perspective based on the upswing of certain disciplines, which by definition seem to have similar subjects of study to neuropsychology; however, given the complexity of the study of the relationship between the behavior and the brain, it leads to a duplicity of efforts that do not add anything to the understanding of the subject matter. On the other hand, from an internal perspective, the main issue appears when diverse theoretical positions are presented within neuropsychology as schools that must stand as if they were the only perspective. To provide a tentative answer, this paper reviews three theoretical approaches within neuropsychology: Russian reflexology and the cultural-historical perspective, connectionism, and cognitive neuropsychology. The conclusion leads towards a set of principles that, as a proposal, should guide the discipline development.